Physical and chemical characterization of the femur during and after the body development period in male and female guinea pigs - Yilmaz, Yuecehan; Aslan Kanmaz, Yesim; Baygeldi, Saime Betuel; Guezel, Baris Can; Karan, Meryem; Guezel, Fuat; Yilmaz, Sadik (Wiley, 2023)
In this study, it was aimed to reveal the physical and chemical characterization of the bone structures during body development periods (prepubertal period, period between adolescence and adulthood) and after (young adult period and old adult period) in male and female guinea pigs. In this study, 40 guinea pigs (20 male, 20 female) were used. Morphometric measurements, X-ray fluorescence (XRF) analysis for mineral levels, Brunauer-Emmett-Teller (BET) analysis for surface area, and porosity analysis were applied to the bones. The male guinea pigs had greater values than females in the other three categories, with the exception of the second group, when the females have higher values in morphometric measurements. Ca levels rose up to the third group, as did P levels in the males, peaking in the third group and declining in the fourth. As with phosphorus, there was a progressive rise in females from the first to the fourth group. Fe, Zn, and Sr elements had the greatest values in both genders in the first group. In all four groups, the females had greater Zn levels than males. The highest Ca/P ratio was found in the third male group and the fourth female group. This study revealed that adolescence, adulthood, and gender are effective in the physical and chemical characterization of bone structure in guinea pigs.
Keywords: BET; femur; guinea pig; morphometric; XRF